Mereka yang Dilacurkan: Studi Kasus Anak-anak Perempuan yang Dilacurkan di Sentra Industri Seks Komersial di Pasuruan, Jawa Timur: Those Who Are Prostituted: A Case Study of Female Children Prostituted in the Commercial Sex Industry Center in Pasuruan, East Java - HJ. Titiek Rohana Hidayati; Nurul Widyawati Islami (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2011)
This research attempts to understand the snow-ball trafficking and prostitution phenomena involving female children in the Commercial Sex Industry Center in Pasuruan, East Java. Beyond being merely an impact of economic problems, especially poverty pressure or gender imbalance caused by patriarchal culture, this study aims to comprehend the commercial sexual exploitation of female children as a form of children's rights violation and a consequence of their defenselessness when facing the domination of capital power and external pressures that support adults. Penelitian ini berupaya memahami fenomena perdagangan manusia (snow-ball trafficking) dan prostitusi terhadap anak perempuan di Sentra Industri Seks Komersial di Pasuruan, Jawa Timur. Lebih dari sekadar dampak masalah ekonomi, terutama tekanan kemiskinan atau ketimpangan gender yang disebabkan oleh budaya patriarkis, studi ini bertujuan untuk memahami eksploitasi seksual komersial yang dialami anak perempuan sebagai bentuk pelanggaran hak anak dan dampak ketidakberdayaan anak perempuan ketika menghadapi dominasi kekuatan kapital serta tekanan kekuatan eksternal yang mendukung orang dewasa.